Pengaruh Perputaran Kas, Pertumbuhan Kredit, dan Kecukupan Modal terhadap Profitabilitas pada Lembaga Perkreditan Desa (LPD) di Kota Denpasar - YULINDA, KADEK RISKA SESIO; BUDIASA, I WAYAN; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022DO - 10.24843/JAA.2022.v11.i01.p32, 2022)
Effect of Cash Turn Over, Credit Growth, and Capital Adequacy on Profitability at Lembaga Perkreditan Desa (LPD) in Denpasar City.  The implementation of Village Credit Institution (LPD) is aimed at improving the standard of living of the village population and supporting village development. One of LPD's efforts to support village development is by channeling funds and services owned by the LPD. The distribution of these funds and services is expected to be able to improve the LPD's financial performance so that it can gain profitability. This study aims to determine the effect of cash turnover, credit growth, and capital adequacy on the profitability of LPDs in Denpasar City. This study uses secondary data obtained from LPDs in Denpasar City, namely the financial reports of all LPDs in Denpasar City for the period 2017-2019. The data obtained were processed using multiple linear regression analysis techniques. The result shows that there are independent variables that have a positive and significant effect on profitability, namely credit growth and capital adequacy. While the cash turnover variable has a negative and significant effect on profitability.